2017
DOI: 10.1007/s11249-017-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

A Deterministic Stress-Activated Model for Tribo-Film Growth and Wear Simulation

Abstract: A new model was developed for the simulation of growth and wear of tribo-chemical films by combining a boundary element method-based contact model and a stress-activated Arrhenius tribo-film growth equation. Using this methodology, it is possible to predict the evolution and steady-state thickness of the tribo-film (selflimitation) at various operating conditions. The model was validated using two cases for which experimental data were available in the literature. The first case is a single microscopic contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 41 publications
3
47
0
Order By: Relevance
“…The above experimental work has inspired models that predict tribofilm growth, removal, and consequent friction and wear in rough surface contacts by numerical modeling, with tribofilm formation governed by the local temperature and stress in a time-evolving system [133,134]. The current main limitation of such models is that while film formation rates can be modelled now with reasonable confidence, the processes and equations that describe film removal are not yet at all well understood or reliable.…”
Section: Mechanochemistry In Tribology: Recent Workmentioning
confidence: 99%
“…The above experimental work has inspired models that predict tribofilm growth, removal, and consequent friction and wear in rough surface contacts by numerical modeling, with tribofilm formation governed by the local temperature and stress in a time-evolving system [133,134]. The current main limitation of such models is that while film formation rates can be modelled now with reasonable confidence, the processes and equations that describe film removal are not yet at all well understood or reliable.…”
Section: Mechanochemistry In Tribology: Recent Workmentioning
confidence: 99%
“…The mechanical and thermal energy present in the contact can be shown to produce an appreciable tribofilm growth rate. Akchurin and Bosman [42] showed that the Arrhenius equation with an additional shear activation energy term can be used to describe the rate limiting step, controlling the growth of the tribofilm as:…”
Section: Micro-scale Tribometrymentioning
confidence: 99%
“…where, is shear stress [Pa], is Boltzmann constant [J/K] and is absolute temperature [K]. The typical values for the factor Γ, activation energy, and activation volume, Δ for growth of a ZDDP film are 0.01 / , 1.12 × 10 −19 and 3.80 × 10 −29 3 respectively [41,42]. For new surface pairs (such as those in the current experiments) some of the asperities deform plastically through running-in conditions.…”
Section: Micro-scale Tribometrymentioning
confidence: 99%
“…The running-in and wear models discussed earlier (Section 2.8) can be combined with a model of tribofilm formation to come to a tribochemical model describing the growth and removal of tribofilms which can predict when equilibrium between growth and removal or the steady state regime is reached [154,[176][177][178][179].…”
Section: Boundary Lubricationmentioning
confidence: 99%
“…This part is missing in the running-in model and should be added to come to a realistic prediction of the transition to severe wear. This can for instance be implemented by following the approaches of [154,[176][177][178][179].…”
Section: Recommendations For Future Researchmentioning
confidence: 99%